1983
DOI: 10.1590/1809-439219831334475
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution of Zooplankton and Physico-Chemical Conditions During a 24-Hour Period in an Amazon Floodplain Lake - Lago Calado, Brazil

Abstract: Summary In May 1980 Lago Calado was 9 meters deep, the water level was rising slowly, and below 4 meters the water was anoxic. Virtually all of the zooplankton was in the oxygenated layer. Adult and juvenile Daphnia gessneri, the most abundant crustacean species, occurred between 0.5 and 4.5 meters. Copepod nauplii tended to occur nearer to the surface, in the 0—2 meter stratum. No clear vertical migration was observed. The epilimnion was undersaturated ( < 40% oxygen) and contained < 0.1 μ M phosphate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

1988
1988
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 7 publications
1
12
0
3
Order By: Relevance
“…Prey availability is not solely responsible for the greater food incidence observed in flooded plants. Zooplankton abundance in lake open areas, may reach 500 ind.l" 1 (Carvalho, 1981;Fisher et al\ 1983;Robertson & Hardy, 1984), being equal or superior to that recorded for aquatic plants by Junk (1973), which indicates 100.000 ind.nr 2 mainly in Paspalum repens concentrations.…”
Section: Feeding Sitesmentioning
confidence: 91%
See 1 more Smart Citation
“…Prey availability is not solely responsible for the greater food incidence observed in flooded plants. Zooplankton abundance in lake open areas, may reach 500 ind.l" 1 (Carvalho, 1981;Fisher et al\ 1983;Robertson & Hardy, 1984), being equal or superior to that recorded for aquatic plants by Junk (1973), which indicates 100.000 ind.nr 2 mainly in Paspalum repens concentrations.…”
Section: Feeding Sitesmentioning
confidence: 91%
“…Cyclical environmental factors of short and medium duration, like distribution of small crustaceans on water column during the day (Fisher et al, 1983), or hydrological cycles (Rabelo, 1999), may influence prey availability. However, it is possible fish larvae show changes due to their diet plasticity or active prey selection (Mérigoux & Ponton, 1998), often as a consequence of occasional food offerings (Goulding, 1980, LoweMcConnel, 1987.…”
Section: Food Contributionmentioning
confidence: 99%
“…In white-water lakes, Fisher et al (1983) did not find clear evidence of vertical movements, but they discovered Daphnia gessneri's preference to remain in deeper layers. The same was observed by Keppeler and Hardy (2004) for most species of the zooplankton community.…”
Section: Introductionmentioning
confidence: 96%
“…The highest number of scientific studies on the richness of this group is concentrated in Brazilian Amazonian region, where floodplain lagoons are far frequent (Thomasson, 1953;Hauer, 1953Hauer, , 1965Hauer, , 1966Gillard, 1967;Marlier, 1967;Koste, 1972;Schaden, 1976;Fisher, 1978;Carvalho, 1983;Brandorff et al, 1982;Koste and Hardy, 1984;Bozelli and Esteves, 1991;Junk and Robertson, 1997). Brandorff and Andrade (1978), Hardy (1980), Koste and Robertson (1983), Hard et al (1984), Fisher et al (1983), , Robertson and Hardy (1984) and Sousa (2003), have emphasized essentially rotifers specific composition of amazonic lagoons. Aproximatelly 300 species of rotifers are known (Koste, unpublished data), in which that diversity upper than the Cladocera and Copepoda in the same region (Day and Davis, 1986).…”
Section: Brazilmentioning
confidence: 99%
“…In Calado Lake, pertaining to Amazon system, Fisher et al (1983) observed at a 9m depth, the zooplankton organisms concentrate in the 4m oxygenated superior layer and disappear in the anoxic inferior layer. Bonecker (1994), in the upper Paraná River floodplain, found higher density values of rotifers in the superficial layers of water column from Baía River, however, in a marginal lagoon, the highest densities were registered in the intermediary and deep layers, suggesting, by the fact of rotifers present migratory vertical movements in short scale, could be avoiding predation through vertical migration.…”
Section: Brazilmentioning
confidence: 99%